Models to Describe the Distribution of Distance Associated with Marriage Migration - Shukla, Kamlesh Kumar (Journal of Institute of Science and Technology, 2015)
The nature of marriage-migration closely linked to social norms and values along with conjugal laws and behavior among the society. In a society where village endogamy is common, there may not be many marriage-migrations. Marriage migration has no influence on size of the population. It is almost a universal custom for bride to move to bridegroom’s home in Indian society. Model is used here based upon distance associated with marriage-migration data of Chandauli district of Uttar Pradesh, India. The suitability of the model is tested with the real data sets and found to be well fitted. The pattern of distance associated with marriage-migration follow the third degree polynomial equation in case of Indian data. Journal of Institute of Science and Technology, 2015, 20(1): 145-147